2014
DOI: 10.1177/1060028013517541
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Dosing and Body Mass Index

Abstract: There is an association between BMI and the TWD of warfarin. This could have dosing implications for both patients and prescribers, as patients with a high BMI will be expected to require higher doses of warfarin to maintain a therapeutic INR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 28 publications
0
36
0
5
Order By: Relevance
“…Wynne found negative correlation between age and dose (r = -0.53; P = < 0.001) and positive correlation between dose and liver volume (r = 0.49; P = 0.002), and that liver volume and age accounted for 43% of dose variability. Another study concluded that lower dose requirements in elderly are attributed to decreased hepatic clearance, 1% decrease per year (99). Increased sensitivity to warfarin in the elderly could be also attributed to reduced vitamin k intake or reduced absorption, which can decrease the capacity of the liver to synthesize clotting factors; or it could simply be a result of polypharmacy that can lead to drug-drug interaction, potentiating the effect of warfarin (100).…”
Section: Effect Of Studied Clinical Factors On Warfarin Dosementioning
confidence: 99%
“…Wynne found negative correlation between age and dose (r = -0.53; P = < 0.001) and positive correlation between dose and liver volume (r = 0.49; P = 0.002), and that liver volume and age accounted for 43% of dose variability. Another study concluded that lower dose requirements in elderly are attributed to decreased hepatic clearance, 1% decrease per year (99). Increased sensitivity to warfarin in the elderly could be also attributed to reduced vitamin k intake or reduced absorption, which can decrease the capacity of the liver to synthesize clotting factors; or it could simply be a result of polypharmacy that can lead to drug-drug interaction, potentiating the effect of warfarin (100).…”
Section: Effect Of Studied Clinical Factors On Warfarin Dosementioning
confidence: 99%
“…Although the pharmacokinetics of warfarin is similar in young and elderly adults, older patients have lower average weight, increasing their warfarin sensitivity, and also the prothrombin time ratio is increased, while adjusted to warfarin dose, suggesting increased pharmacodynamic effects as well . BMI influences the mean daily warfarin dose, although large interindividual variations exist within a BMI group . In our limited sample, with mean BMI only moderately elevated, no effect of BMI was observed on the warfarin dose requirement.…”
Section: Discussionmentioning
confidence: 52%
“…Copyright: © 2016 Gossell-Williams et al weight [17,18,19], there is no evidence from this study to suggest such an association.…”
Section: Therapeutic Anticoagulation Prevalence Among Patients Of a Cmentioning
confidence: 64%